The effectiveness of Game-Based Science Learning (GBSL) to improve students’ academic achievement: A meta-analysis of current research from 2010 to 2017 - Heru Setiawan; Shane Phillipson (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2019)
This study identifies the effectiveness of game-based science learning (GBSL) for improving students’ learning outcomes by conducting a literature review of the current research from 2010 to 2017. This study also explores the correlation between variation in school level and year of publication on GBSL effect size. Data were collected from peer-reviewed journal articles published in educational databases including ERIC (Educational Research Information Centre), Springer Link, ProQuest education journal, and A+ education. Seven inclusion criteria were used to select relevant studies. Comprehensive Meta-Analysis (CMA 2.0) was used to analyze the data. This study finds that (1) GBSL intervention has a statistically significant effect on students' learning outcomes with a higher average on the effect size of the experimental group (41.12) than the control group (37.07). The mean of the reviewed studies’ effect size is 0.667 in the medium category. (2) The implementation of GBSL in secondary school has a bigger average effect size than in elementary school. Year of publication and effect size has a low positive correlation with a coefficient of correlation 0.40.